Simulation of the crack development in coal without confining stress under ultrasonic wave treatment. (1st October 2017) - Shi, Qingmin; Qin, Yong; Li, Jiuqing; Wang, Ziwei; Zhang, Minjian; Song, Xuejuan
Highlights: Ultrasonic waves can be used to enhance the permeability of CBM reservoirs. Cleats and bedding plane control crack development under ultrasonic stimulation. Coal fractures along bedding planes after ultrasonic stimulation for 360 h. The heterogeneous components boost coal to fracture along the bedding plane. Abstract: Ultrasonic waves can potentially be used to improve the permeability of low-permeability coalbed methane (CBM) reservoirs by enhancing cleats propagation and new cracks generation. Two polished blocks of semi-anthracite coal were subjected to ultrasonic waves for 360 h without confining stress. The variations in cracks development due to the effects of original cracks (especially face cleats) and of coal bedding are investigated by an optical microscope, a scanning electron microscope, and an ultrasonic analyzer. Ultrasonic waves induce crack propagation along face cleats, butt cleats, and coal bedding planes. The cracks are generated especially in the bedding planes and ultimately break coal into two parts with a rugged crack surface. Cracks primarily propagate in desmocollinite along cleats in the raw coal in the earlier stage of ultrasonic vibration. In the latter stage, crack propagation primarily occurs in fusinite or at the interfaces along the direction of the coal bedding. The surface crack ratio and acoustic attenuation measured by an ultrasonic analyzer indicate that cracks propagate along face cleats and bedding in the first 36 h of vibration more rapidly than in the latter stage. Ultrasonic waves are loaded at the crack tip, where concentrated stress is generated, promoting crack propagation along face and butt cleats under periodic tensile and compressive stresses. Cracks and the interfaces between different compositional features in coal are mechanically weak planes. The macerals and minerals in bedding planes have large contact areas and various degrees of microhardness. Owing to the effects of different wave impedances of the components, the reflected stress fields and transmitted stress fields differ on both sides of the component interface. This periodic stress difference at a mechanically weak interface generates microcracks in bedding planes and the cracks ultimately develop into the uneven crack surface through the entire coal.